The Most Influential Publications in Obstetric Anesthesiology, 1998-2017: Utilizing the Delphi Method for Expert Consensus. Issue 4 (December 2020) - Reale, S.C.; Tsen, L.C.; Camann, W.R.; Bateman, B.T.; Farber, M.K.
Abstract : ( Anesth Analg . 2020;131:239–244) Obstetric anesthesiology has seen many advances in the past 20 years. Identifying publications that have substantially influenced not only the practice of obstetric anesthesiology but also that of medicine, have relied upon analyses of bibliometric data or cited references, or a nomination process by select experts or panelists. This study sought to use the Delphi method to identify the most influential publications in the field of obstetric anesthesiology.